Spirituality and Sustainability: How Local Wisdom in Desa Wates is Paving the Way for Cultural and Environmental Preservation - Bondan Satrio Wicaksono; Daud Rismana; Lusiana Dewi; Serlyta Indriyanti; Frieska Putri Fanesa; Shinta Eka Ramadhani; Siti Wulandari; Tian Lailatul Badriah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Local wisdom functions as a bridge between spirituality and sustainable living, especially in rural communities such as Wates Village. This article explores the integral role of local wisdom in maintaining cultural heritage and environmental balance in villages. Through in-depth study of traditional practices, such as the ritual of recitation of petilasan, earth almsgiving, and others. this research highlights how these customs are deeply rooted in spiritual beliefs that encourage ecological conservation. This paper argues that local wisdom in Wates Village not only strengthens cultural identity but also provides practical solutions for sustainable development. By examining how spirituality influences conservation efforts and community resilience, this research highlights the broader implications of local wisdom in addressing modern challenges. These findings show that the application of traditional knowledge systems can make a significant contribution to cultural continuity and environmental sustainability, as well as providing valuable insights for communities facing the pressures of globalization and environmental degradation. This research uses an interview method by going directly to meet the community and mingle so they can find out about the local wisdom that exists in this place. The aim of this research is to find out how much local wisdom exists in this village so that we KKN 102 students understand more about the culture in this village.